2014
DOI: 10.1002/ana.24050
|View full text |Cite
|
Sign up to set email alerts
|

Novel hypoglycemic injury mechanism: N‐methyl‐D‐aspartate receptor–mediated white matter damage

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Aglycemia was produced by switching to 0 glucose ACSF. Supra-maximal compound action potentials (CAPs) were elicited using suction electrodes and axon function was quantified as the area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…Recently, it has been demonstrated that aglycemic white matter injury arose from N-methyl-D-aspartate receptors (NMDAR) activated by aspartate, not glutamate, in animal experiments (NMDAR 'excitotoxic' injury). DWI lesions in white matter may be caused by NMDAR activated by aspartate in hypoglycemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that aglycemic white matter injury arose from N-methyl-D-aspartate receptors (NMDAR) activated by aspartate, not glutamate, in animal experiments (NMDAR 'excitotoxic' injury). DWI lesions in white matter may be caused by NMDAR activated by aspartate in hypoglycemia [17].…”
Section: Discussionmentioning
confidence: 99%
“…9-3). These complex cellular interactions during ischemia or other disruptions in energy metabolism 22 have just begun to be explored in white matter. Ischemia will, of course, eventually affect all the elements in white matter, leading to axon-glial interactions that are important for understanding how injury occurs.…”
Section: White Matter Anatomy and Physiologymentioning
confidence: 99%
“…42 Potential nonsynaptic sources for toxic glutamate release within ischemic white matter are axons, 45 astrocytes, 122,123 and oligodendrocytes. 22 In several experimental situations, AMPA/KA receptor blockade has been shown to protect axons as well as glial cells. The release is mediated by reverse Na + -dependent glutamate transport, and astrocytes are the cells with the highest density of these transporters.…”
Section: Excitotoxic Pathways Injure Glia In White Mattermentioning
confidence: 99%
“…The ATP production decreases leading to membrane depolarization and aspartate‐mediated activation of NMDA receptors (Yang et al. ), opening of voltage gated Ca 2+ channels and reversal of the Na + ‐Ca 2+ exchanger (Brown et al. ), all of which lead to toxic Ca 2+ influx into axons.…”
Section: Introductionmentioning
confidence: 99%